Pembrolizumab alone or with chemotherapy for metastatic non-small-cell lung cancer: A systematic review and network meta-analysis. (May 2022) - Udayakumar, Suji; Parmar, Ambica; Leighl, Natasha B.; Everest, Louis; Arciero, Vanessa S.; Santos, Seanthel Delos; Rahmadian, Amanda; Doherty, Mark K.; Chan, Kelvin K.W.
Abstract: Pembrolizumab monotherapy has replaced chemotherapy as first-line treatment for patients with metastatic non-small-cell lung cancer with tumor programmed death-ligand 1 expression ≥ 50%. The benefit of chemotherapy combined with pembrolizumab, as compared to pembrolizumab monotherapy, remains uncertain. This systematic review and network meta-analysis aimed to compare these therapies through a network of randomized controlled trials. Endpoints evaluated were progression-free survival (PFS) and overall survival (OS) expressed as hazard ratio (HR) and restricted mean survival time (RMST) through reconstruction of individual patient data from Kaplan-Meier curves, and objective response rate and adverse events. Four trials were included. Through HR and RMST, combination therapy demonstrated longer PFS and similar OS as compared to pembrolizumab monotherapy. Combination therapy was associated with an increase in response rate and adverse events. Thus, combination therapy can be considered when rapid response or prevention of rapid progression is needed. Further evidence to directly compare these therapies is required. Graphical Abstract: ga1 Highlights: A network meta-analysis allows for the indirect comparison of treatments. Restricted mean survival time is a robust survival measure for immunotherapies. Combining chemotherapy and pembrolizumab may improve progression-free survival. Pembrolizumab with or without chemotherapy have similar overall survival. This combination can be considered for rapid response or prevention of rapid progression.